حوكمة منظومة الرقابة الشرعية في المؤسسات المالية الإسلامية: بين تطبيق المعاصرين ونظرة المؤسسين - ابن عيسي، داود سلمان عيسى (الجامعة الإسلامية بغزة - عمادة البحث العلمي والدراسات العليا, 2019)
تناول هذا البحث موضوع: حوكمة الرقابة الشرعية ومدى ملائمة تطبيق بنودها على المنظومة الرقابية في المصارف الإسلامية، والنظر في رؤية المؤسسين مع واقع التطبيق. وجاءت في مقدمة، ومبحثين، وخاتمة، فذكرت في المقدمة وظائف المدقق الشرعي وأهمية الحوكمة في الرقابة الشرعية، تم عرضت في المبحث الأول دور الجهات الرقابية والمؤسسين وأثرهم على حوكمة المصارف الإسلامية، وأفردت المبحث الثاني في تطبيق المعايير الشرعية للحوكمة وأثر توحيد المرجعية الشرعية، وختمت بحثي ببيان أبرز النتائج التي خلصت إليها في هذ البحث مع ذكر التوصيات. وأبرز ما أظهره هذا البحث: مفاهيم الحوكمة، وبيان دور الجهات الرقابية في حوكمة المصارف الإسلامية، وعرض المعيار الشرعي للحوكمة، وبيان مدى تطابقه على الرقابة الشرعية في المصارف الإسلامية، كما بينت في هذا البحث أثر توحيد المرجعية الشرعية على حوكمة الرقابة الشرعية، مع بيان تطبيقات بنود الحوكمة. وقد توصلت في هذا البحث إلى أمور أهمها: أن الدعوة لتوحيد المرجعية الشرعية وجعلها مركزية قد يهدم الاقتصاد الإسلامي ويعود به إلى الجمود، وكذلك الممارسة الخاطئة لبعض العاملين في المصارف والمؤسسات المالية هو خروج عن المقاصد التي نادى بها المؤسسون، وأوصيت بإنشاء لجنة حكومية تجمع خبراء في جميع المجالات الاقتصادية والقانونية والمحاسبية والشرعية لاختيار أعضاء هيئات رقابية شرعية للشركات الإسلامية.
The aim of this paper is to review the Sharia governance supervisory system and to discuss the suitability of its terms and the extent of compliance with supervisory system in Islamic financial institutions. The paper has a particular focus on the founders' views on practical works of Sharia governance supervisory system This paper is structured in four parts: first, Introduction; then first and second sections; and finally, Conclusion. The first section provides sufficient detail for the roles and impact of regulatory bodies and the founders on the governance of Islamic banks. The second section discusses the use of Sharia governance standards and the impact of unifying or standardization of Sharia practices. The Conclusion section presents the outcome of the study by summarizing the findings. This paper highlights the concepts of governance, and the role of regulatory bodies or authorities regarding the governance of Islamic banks. It also discusses Sharia standard of governance and the extent of its compliance with sharia supervisory in Islamic banks. Furthermore, this paper outlines the impact of standardization of sharia practices on sharia supervisory governance. The paper also outlines the implementation of governance provisions. Additionally, some key issues pertaining to the need of standardization of Sharia governance practices in Islamic financial institutions are addressed to pay further attention to the issue of centrality which may lead to serious deterioration of Islamic economics, as well as the wrong practices of some employees in banks or financial institutions which are incompatible with the purposes advocated by the founders. Finally, I strongly recommend that the government must establish a committee comprises economic, legal, accounting and sharia experts to select members of regulatory bodies in companies with sharia compliance status.
Keywords: الإدارة المالية -- المؤسسات المالية -- الاقتصاد الإسلامي -- الرقابة المالية